Fine-structured morphology of a silicon steel sheet after laser surface alloying of Sb powder - Steiner Petrovič, Darja (Strojniški vestnik, 2014)
An experiment was designed to investigate the feasibility of surface modifying a fully processed, non-oriented, electrical steel sheet withantimony (Sb) using laser surface alloying (LSA). The post-exposure microstructural characterization of the modified steel sheet was performedusing light microscopy (LM) and field-emission scanning electron microscopy (FE-SEM/EDS). Microhardness measurements confirmed the differences in the microhardness profile along the depth direction as a result of the applied laser-alloying treatment. The additive nature of the laser treatment and the specific cooling conditions create unique solidification conditions that ensure not only a high microhardness of approximately 400 HV0.1of the modified layer, but also its fine-structured morphology.
Keywords: antimon; antimony; lasersko površinsko legiranje; mikrostrukture; morfologija; neorientirana elektropločevina; silicijeva jekla; strjevanje